Tanaman Obat Indonesia sebagai Kandidat Antikanker Serviks: Systematic Review - Dhara Almira Desideria; Nuraisya Rahmadina Putri; Muhammad Fauzil Adhim; Asep Kadarohman (Yayasan Literasi Sains Indonesia, 2026)
Cervical cancer remains a leading cause of death among women worldwide, primarily due to Human Papilloma Virus (HPV) infection that activates oncogenic proteins E6 and E7. The use of synthetic chemotherapy often causes severe side effects, creating an urgent need for safer and more effective natural alternatives. This review aims to compare several herbal plants with reported anticancer activity against cervical cancer, including basil (Ocimum basilicum L.), soursop seeds (Annona muricata L.), Chinese petai leaves (Leucaena leucocephala), jengkol bark (Archidendron jiringa), parijoto fruit (Medinilla speciosa), kuhung-kuhung leaves (Crotalaria striata), and lawang bark (Cinnamomum cullilawan). The study also analyzes the extraction solvents used and their influence on cytotoxic effectiveness. Literature searches were conducted using Publish or Perish and Google Scholar with keywords “HeLa cells,” “cervical cancer,” “anticancer,” “apoptosis,” and “plants,” covering publications from 2015–2025. From 100 screened papers, 5 articles met the inclusion criteria. The results indicate that the combination of Chinese petai leaf and jengkol bark extracts showed the strongest cytotoxic activity through synergistic interactions of alkaloids, flavonoids, and tannins. Soursop leaves also act by inhibiting complex I in mitochondria and reduce the ATP production in cytoplasm, while basil exhibited moderate activity through oxidative stress induction. In contrast, kuhung-kuhung leaves and lawang bark displayed weak effects. Overall, the findings suggest that anticancer activity is strongly influenced by secondary metabolite content and extraction methods, supporting the potential of Indonesian herbal plants as promising candidates for cervical cancer therapy.